Stress and coping strategies among Balkan mothers of children with developmental disorders - Marisavljević, Maša; Petrović, Nikola; Jovanović, Olja; Ćirović, Milica; Stanojević, Nina; Folić, Nevena (Primenjena psihologija, 2024)
This study explored stress in Balkan parents of children with developmental disorders (DD), taking into account the type of child’s DD, sociodemographic factors, and coping strategies. Sample comprised 139 mothers from Serbia (42%), Montenegro (27%), Bosnia and Herzegovina (14%), Croatia (16%), and Slovenia (2%), whose children were diagnosed with specific developmental disorders of speech and language (37%), autism spectrum disorders (39%) and mixed specific developmental disorders (24%). Mothers completed the Parenting Stress Index-SF and Brief COPE, and provided information on sociodemographic characteristics. The one-way ANOVA revealed that mothers of children with ASD reported the highest stress intensity. Linear regression suggests that having a child with autism spectrum disorder, lower education, and the use of Self-blame contribute to the prediction of stress. The results of several mediation analyses indicate that Religion and Behavioral disengagement mediate the relationship between parental stress and the child’s age: parents of older children with DD show a greater tendency to use these coping strategies, which consequently leads to higher stress levels.